Fast assessment of canine hearing using high click-rate BAER - Wilson, W. J.; Mills, P. C.; Bradley, A. P.; Peloe, M. A.; Smith, A. W. B.; Dzulkarnain, Ahmad Aidil Arafat (Balliere Tindall, 2011)
The aim of this study was to determine if high stimulus repetition rates could reduce the time taken to obtain brainstem auditory evoked response (BAER) waveforms of equivalent quality in dogs. Click-evoked BAER waveforms were obtained from nine healthy, adult, mixed-breed dogs at stimulus intensities of 70, 60, 50 and 40 decibels (normal hearing level) (dBnHL) and stimulus repetition rates of 11, 33 and 91 clicks-per-second (cps). The quality of the BAER waveforms was kept constant by ensuring all waveforms achieved the same signal-to-noise (SNR), as shown by their Fsp value of 3.1. Increasing the stimulus repetition rate from 11 to 91. Hz significantly (P<0.01) reduced the median time to obtain BAER waveforms of equivalent quality by 3.29-14.07. s per waveform, or alternatively, increased the recording speed by 4.6-13.7 times per waveform (depending on the stimulus intensity). The use of high stimulus repetition rate BAER shows significant promise for the rapid assessment of auditory function in dogs.